Increased genetic marker density reveals high levels of admixture between red deer and introduced Japanese sika in Kintyre, Scotland. (6th November 2019) - McFarlane, S. Eryn; Hunter, Darren C.; Senn, Helen V.; Smith, Stephanie L.; Holland, Rebecca; Huisman, Jisca; Pemberton, Josephine M.
Abstract: Hybridization is a natural process at species range boundaries, but increasing numbers of species are hybridizing due to direct or indirect human activities. In such cases of anthropogenic hybridization, subsequent introgression can threaten the survival of native species. To date, many such systems have been studied with too few genetic markers to assess the level of threat resulting from advanced backcrossing. Here, we use 44, 999 single nucleotide polymorphisms (SNPs) and the ADMIXTURE program to study two areas of Scotland where a panel of 22 diagnostic microsatellites previously identified introgression between native red deer ( Cervus elaphus ) and introduced Japanese sika ( Cervus nippon ). In Kintyre, we reclassify 26% of deer from the pure species categories to the hybrid category whereas in the NW Highlands we only reclassify 2%. As expected, the reclassified individuals are mostly advanced backcrosses. We also investigate the ability of marker panels selected on different posterior allele frequency criteria to find hybrids assigned by the full marker set and show that in our data, ancestry informative markers (i.e. those that are highly differentiated between the species, but not fixed) are better than diagnostic markers (those markers that are fixed between the species) because they are more evenly distributed in the genome. Diagnostic loci are concentrated on the X chromosome to the detriment of autosomal coverage.